Influence of Supplementing Parsley and Cilantro Extracts on Sensory Parameters of Soft Cheese with Highlighting on Their Antibacterial Impact - Abdel-Salam, Ayah, B.; Emam, Shimaa R.; Saad, Mena F.; Soliman, Neveen S.M. (Journal of Advanced Veterinary Research, 2023)
Â  The study was achieved to show the influence of supplementing different concentrations of parsley and cilantro extracts on sensory and microbiological parameters of soft cheese during 2 weeks of storage. The antibacterial activity of crude extracts and the Minimum Inhibitory Concentration (MIC) of both plants were determined. Also, a study of food poisoning bacteria survival in artificially contaminated soft cheese. The Escherichia coli (E. coli), Salmonella Typhimurium (S. Typhimurium), and Staphylococcus aureus (S. aureus) were sensitive to oil extract (0.5%) of both plants, while E. coli and S. Typhimurium were sensitive to methanol extract (5.0%) of cilantro based on MIC. The oil extract (0.5%) of parsley had a significant (p<0.05) improving effect on the sensory parameters of samples throughout storage. In E. coli and S. Typhimurium contaminated samples, there was a significant difference (p<0.05) between samples with the oil extract (0.25% and 0.5%) of parsley and samples without extracts for pH value at end of the storage period. Based on the survival results, S. Typhimurium could not be isolated from all cheese samples with oil extract (0.5%) of cilantro on days 12 and 14 of storage, while E. coli count was reduced to 2.85 and 2.36 log CFU/g in cheeses with oil extract (0.25%) of parsley and cilantro, respectively. The S. aureus could not be isolated from all cheese samples with oil extract (0.5%) of parsley and cilantro from day eight till the end of the storage period. Results of the study recommended the use of these plants oil extracts to improve soft cheese safety and quality. This trial of the survival of food poisoning bacteria in the soft cheese supplemented by oil and methanol extracts of parsley and cilantro is one of the fewest studies, particularly in the Middle East.